A new k-interval optimization technique for atmospheric upwelling radiance calculation in infrared absorption bands. (July 2015) - Zhang, Yin; Hao, Shijing; Yu, Kun; Cong, Mingyu
Abstract: A new optimization technique is proposed to generate the k -interval parameters including the quadrature weights and their corresponding equivalent absorption coefficients when using correlated k -distribution method for computations of spectrally integrated atmospheric upwelling radiances in infrared absorption bands. The main feature of this technique is the introduction of the upwelling contribution function (UCF) both in expressing the atmospheric upwelling radiance and in constructing the merit function for fitting, so that the optimization for the band radiance smoothly turns into the optimization for the band UCF of each atmospheric sublayer. The performance of the proposed technique is illustrated by comparing with the Δlog( k ) technique and the Gauss–Legendre quadrature technique at three different band settings in both the US standard atmosphere and the tropical atmosphere, and the line-by-line results are treated as the reference. Results show that there are less relative errors by the proposed optimization technique than by the other two techniques under the same number of k -intervals. In most cases, the computational efficiency can be improved by more than 10% under the same precision requirement in upwelling radiance calculations, and even 80% in some preferable conditions. Highlights: A k -interval optimization method for infrared absorption bands is presented. Upwelling contribution function is introduced for fitting. Only quadrature weights are involved in the optimization. Performance is superior to the Δlog( k ) method and the Gaussian quadrature method.